2020
DOI: 10.1186/s13148-020-00932-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of FKBP5 in South African women: associations with obesity and insulin resistance

Abstract: Background Disruption of the hypothalamic–pituitary–adrenal (HPA) axis, a neuroendocrine system associated with the stress response, has been hypothesized to contribute to obesity development. This may be mediated through epigenetic modulation of HPA axis-regulatory genes in response to metabolic stressors. The aim of this study was to investigate adipose tissue depot-specific DNA methylation differences in the glucocorticoid receptor (GR) and its co-chaperone, FK506-binding protein 51 kDa (FKB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Association between DNA methylation with fasting glucose were found for ADIPOQ (positive association) and TNFA (negative association), although there is some contradicting information regarding ADIPOQ since another study found no relationship between ADIPOQ and any glycemic parameters ( 53 ). HOMA-IR showed a positive correlation with methylation at INSR , SLC2A4 ( 56 ) and FKBP5 ( 57 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Association between DNA methylation with fasting glucose were found for ADIPOQ (positive association) and TNFA (negative association), although there is some contradicting information regarding ADIPOQ since another study found no relationship between ADIPOQ and any glycemic parameters ( 53 ). HOMA-IR showed a positive correlation with methylation at INSR , SLC2A4 ( 56 ) and FKBP5 ( 57 ).…”
Section: Resultsmentioning
confidence: 97%
“…Altogether, these studies profiled DNA methylation for 14 genes with established roles in AT and/or glycemic control, ranging from adipokines ( TNFA, ADIPOQ ) to a glucose transporter ( SLC2A4 ). Of these 14 genes ( Table 1 ), ADIPOQ and TNFA had gene methylation frequency altered in MUHO ( 59 ), whilst FGF21 ( 58 ), INSR, SLC2A4 ( 56 ) and FKBP5 ( 57 ) were associated with DMRs that correlated negatively with gene expression. Meanwhile, MCP1 ( 59 ), HIF3A ( 55 ), LEP ( 53 ), C3 ( 52 ), SREBF , ABCG1 ( 54 ), PIK3R1 ( 56 ) and GR ( 57 ) showed no differences between subjects with MUHO and NW/MHO controls, or showed no correlation with glycemic parameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the relationship between obesity and insulin resistance, Aneta Cierzniak et al [ 33 ] collected VAT and SAT from 45 patients undergoing abdominal surgery. Tarryn Willmer et al [ 34 ] obtained abdominal SAT and gluteal SAT from 27 obese and 27 normal weight urban-dwelling South African women and found that the methylation level of FK506-binding protein 51 kDa (FKBP5) gene was associated with obesity and insulin resistance. In conclusion, the sample size of this study is moderate, and the results of this study have a certain reference value, which can provide a theoretical basis for finding targets for the treatment of obesity.…”
Section: Discussionmentioning
confidence: 99%